Self-assembled dithiocarbamate-copper(II) macrocycles for electrochemical anion recognition - Beer, P; Berry, N; Drew, M; Fox, O; Padilla-Tosta, M; Patell, S (2001)
A novel family of redox-active dinuclear copper(II)-based macrocycles self-assembled from dithiocarbamate ligands has been synthesised; a naphthyl-spaced complex exhibits selective electrochemical recognition of perrhenate and dihydrogenphosphate anions.